One world, one day - Kerley, Barbara (Washington, D.C. : National Geographic, 2009)
This beautiful photo book follows the course of one day in our world. Sunrise to sunset is captured in the essential things we all do daily, wherever we live in the world, and in the different ways we do them. The first meal of the day will take on a whole new dimension for American kids as an American pancake breakfast is contrasted with porridge in North Korea and churros in Spain.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Notable Social Studies Trade Books for Young People, 2010
Description based on print version record.
Keywords: Children -- Social life and customs -- Juvenile literature; Children -- Pictorial works -- Juvenile literature; Children; Children -- Social life and customs; Electronic books- OSLIS; Electronic books